2017
DOI: 10.1159/000484452
|View full text |Cite
|
Sign up to set email alerts
|

Maternally Expressed Gene 3 (MEG3) Enhances PC12 Cell Hypoxia Injury by Targeting MiR-147

Abstract: Background/Aims: Cerebral ischemia often leads to breakdown of blood–brain barrier (BBB) and vasogenic edema. It remains to be established whether MEG3 is responsible for the hypoxic damage in neural cells. This study aimed to investigate the role of MEG3 in the hypoxia-induced injuries of PC12 cells. Methods: The PC12 cells were seeded and cultured under hypoxia and normoxia culture conditions. The cell viability determined by trypan blue exclusion, apoptosis using propidium iodide (PI) and fluorescein isothi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…Abnormally expressed miRs have been proven to play an important part in diagnosis, prognosis and prediction of treatment outcome [32]. As previously reported, miR-9a-5p may provide a promising target in alleviating MCAO-induced ischemia injury; down-regulation of miR-147 was responsible for the aggravation of hypoxial injury in PC12 cells [33, 34]. Stable hsa-miR-381 expression in serum was suggested to offer a new and prospective diagnostic biomarker, and anti-hsa-miR-381 could be an ideal target for glioma treatment, further indicating that miR-381 could participate in the activities of the nervous system [15].…”
Section: Discussionmentioning
confidence: 98%
“…Abnormally expressed miRs have been proven to play an important part in diagnosis, prognosis and prediction of treatment outcome [32]. As previously reported, miR-9a-5p may provide a promising target in alleviating MCAO-induced ischemia injury; down-regulation of miR-147 was responsible for the aggravation of hypoxial injury in PC12 cells [33, 34]. Stable hsa-miR-381 expression in serum was suggested to offer a new and prospective diagnostic biomarker, and anti-hsa-miR-381 could be an ideal target for glioma treatment, further indicating that miR-381 could participate in the activities of the nervous system [15].…”
Section: Discussionmentioning
confidence: 98%
“…MEG3 is an imprinted gene within the DLK1-MEG3 locus located at human chromosome 14q32, which is the first lncRNA verified to act as a tumor suppressor and exert its anti-proliferative role through multiple signaling pathways [16,17,37,38]. Wei et al have revealed that MEG3 can inhibit proliferation and metastasis of gastric cancer via the p53 signaling pathway [39].…”
Section: Discussionmentioning
confidence: 99%
“…Maternally expressed gene 3 (MEG3) is the first lncRNA that has been shown to function as a tumor suppressor and inhibit cell proliferation in numerous human cancer cell lines, and it is expressed in many normal human tissues [15][16][17]. Loss of MEG3 expression has been identified in many human tumors, including cervical cancer [18], retinoblastoma [19], ovarian carcinoma [20], gastric cancer [21], germ cell tumor [22], and squamous cell carcinoma [23], and such loss is indicative of poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation of this is that there might be an unknown gene that is targeted by miR-147, and the effect of MEG3 and miR-147 on cell apoptosis might be mediated by this gene [30]. For example, Han et al, found that MEG3 aggravated hypoxia injury in PC12 cells by down-regulating miR-147, and miR-147 further negatively regulated Sox2 expression [31]. It should be noted that our co-immunoprecipitation results showed that JAK2 could interact with TYK2 through MEG3, suggesting that JAK2 might be the gene contributing to the negative interaction between MEG3 and mi147.…”
Section: Discussionmentioning
confidence: 99%